2022
DOI: 10.1186/s13098-022-00834-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visceral fat lipolysis adaptation to high-intensity interval training in obesity-prone and obesity-resistant rats

Abstract: Background/objectives Visceral obesity is one of the key features of metabolic syndrome. High-intensity interval training (HIIT) could effectively reduce visceral fat, but its effects show strong heterogeneity in populations with different degrees of obesity. The mechanism may be related to the differential adaptation to training between obesity phenotypes, namely obesity prone (OP) and obesity resistant (OR). The aim of the present study was to compare adaptive changes of visceral adipose lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Hypertension, insulin resistance, and dyslipidemia are all influenced by visceral fat ( 34 ). Visceral fat has also been associated with increased activity of sympathetic nervous system, one of the most important causes of hypertension ( 35 ). Instead of indicating heavier body weight, LAP may better reflect the accumulation of total fat in the body and the function of visceral fat ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, insulin resistance, and dyslipidemia are all influenced by visceral fat ( 34 ). Visceral fat has also been associated with increased activity of sympathetic nervous system, one of the most important causes of hypertension ( 35 ). Instead of indicating heavier body weight, LAP may better reflect the accumulation of total fat in the body and the function of visceral fat ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that HIIT can further stimulate the secretion of catecholamines compared with moderate-intensity continuous training (MICT), which is more conducive to reducing visceral fat [8]. It is mostly related to lipolysis degree within visceral adipose tissues upon increased metabolic demands relative to subcutaneous fat [10], partly attributable to the higher activity of lipolytic hormones and lower activity of antilipolytic counterparts in the visceral adipocytes [11,12].…”
Section: Introductionmentioning
confidence: 99%